The Qur’anic Concept of “Shākilah” (Disposition): From the Notion of Predestinarianism to the Reality of Secondary Creation - Mohsen Nouraei; Javad Irvani (آموزه‌های قرآنی)
The Holy Qurʾān presents individual actions as being based on one’s “shākilah” (Arabic: شاکِله, disposition), which has led to a variety of interpretations and conclusions. If “shākilah” is rooted in the creation of the individual, the diversity of human natures and a form of determinism in the manifestation of behaviors may be potential outcomes. Conversely, if “shākilah” is a self-constructed phenomenon, uncovering the underlying factors and influences will become significant. This article aims to explore and articulate the concept and purpose of “shākilah,” as well as the factors contributing to its formation, utilizing a descriptive-analytical approach. The study’s findings indicate that human shākilah represents the self-constructed moral personality and secondary temperament of an individual, shaped by a variety of influences, including genetic factors, hereditary traits, personality backgrounds, instincts, innate tendencies, intellectual abilities, social environment and culture, as well as the individual’s element of free will and choice. Therefore, while determinism in actions is dismissed, the role of ethics and education in shaping “shākilah,” as well as the reciprocal influence of “shākilah” on behavior, clarifies the issues of intention and its purity, as well as the concept of eternal life. The results of this research have clear implications in various fields of Islamic studies, such as determinism and free will, eternal life (immortality), the nature and philosophy of ethics, educational sciences, and some issues in moral theology, including sincerity.